MODEL PEMBERDAYAAN MASYARAKAT USAHA KECIL MENENGAH (UKM) DI KAWASAN EKS LOKALISASI DOLLY SURABAYA - Arini Sulistyowati; Dwi Wahyu Prasetyono (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
This research was intended to identify community empowerment program for the ex “Dolly” localization, Surabaya to the development of empowerment models which are effective for the affected communities of the localization. The closure of the localization of in surabaya (and some other cities) left behind problems on the affected communities (fuel price hike worried investors localization of extricating a person who begins) who termarginalyze from the economic life of cause have lost employment opportunities. Needed capable of bridge empowerment intermediate profession affected communities on a new job in normal life. Empowerment is the provision of capacity to target that can and able to solve the matter in more independent. Public empowerment be able run well and be more successful if the group seen as collective the community target. On that perspective be related to be concerned with community ecology context, where success empowerment also determinated by intervation of the concerned with character of society. Institutional ecology perspective allows the development of partisipatori of subjects in empowerment process. The research is qualitative study was conducted within the framework of post positivist paradigm. Approach that is used is phenomenology, intented capturing reality and meaning, and reveal that is behind the empowerment process to the people who affected communities of the cover-up were “Dolly” localization. The results of the analysis data expected to model empowerment to develop effective in the localization affected communities in particular.